The Heme Oxygenase/Biliverdin Reductase System as Effector of the Neuroprotective Outcomes of Herb-Based Nutritional Supplements - Mhillaj, Emanuela; Cuomo, Vincenzo; Trabace, Luigia; Mancuso, Cesare (Frontiers in Pharmacology, 2019)
Over the last few years, several preclinical studies have shown that some herbal products, such as ferulic acid, ginkgo biloba and resveratrol, exert neuroprotective effects through the modulation of the heme oxygenase/biliverdin reductase system. Unfortunately, sufficient data supporting the shift of knowledge from preclinical studies to humans, particularly in neurodegenerative diseases, are not yet available in the literature. The purpose of this review is to summarize the studies and the main results achieved on the potential therapeutic role of the interaction between the heme oxygenase/biliverdin reductase system with ferulic acid, ginkgo biloba and resveratrol. Some critical issues have also been reported, mainly concerning the safety profile and the toxicological sequelae associated to the supplementation with the herbs mentioned above, based on both current literature and specific reports issued by the competent Regulatory Authorities.